Preliminary Checklist of Malaxidinae and Liparidinae Representatives (Orchidaceae, Malaxideae) from Bali and Lombok Islands (Indonesia) with New Records - Hanna B. Margońska; Jeffrey Champion; Monika M. Lipińska (Diversity, 2022)
Bali and Lombok are well known as popular touristic destinations. Both islands are accessible for potential floristic research, but surprisingly, information on their orchid flora is rather scarce and random. During our visits, among other orchid groups, we had an opportunity to observe several representatives of the tribe Malaxideae, which is considered to be one of the biggest and most interesting orchid groups with over 1700 taxa (including synonyms). In this paper, we present the first attempt at organizing the knowledge about these unique, often underestimated, orchids in Bali and Lombok, and we report several new records for both islands. For Bali, there are six from the genus Crepidium and four from Liparis sensu lato, and for Lombok, one from Crepidium and three from Liparis sensu lato.